ANALISIS HUKUM TERHADAP HAK EKONOMI PENCIPTA KARYA MUSIK DAN LAGU YANG DI COVER VERSION PADA PLATFORM DIGITAL - Adi Juardi; Martin Roestamy; Nurwati (JURNAL ILMIAH LIVING LAW, 2023)
The most basic problem is that there is no regulation regarding royalty rates for performance rights on digital platforms, while the royalty rates used so far depend on each platform to the CMO. Many cover version musicians commercialize their work without the permission of the original creator, resulting in copyright infringement. The research used is empirical juridical using legislation and interview approaches. The conclusion is that due to the large potential for copyright infringement on the cover version, it must first obtain permission from the creator, Article 9 (2). Departing from the theory of development, the Copyright Law and Government Regulation Number 56 of 2021 must be able to follow existing developments. There needs to be clear rules regarding royalty rates on digital platforms, as of this writing, there are no statutory regulations or their derivatives that regulate it. About sharing royalties for copyright creators for music and songs included in digital platforms. If you look at the Utilitarianism theory carried out by WAMI's CMO for music royalties and songwriters on digital platforms, then the distribution of royalties is part of the legal goal of this theory, which is to provide benefits and happiness to as many people as possible.